Beyond boundaries: Navigating fluidity, power dynamics, and erasure in contemporary lesbian identities - Eduarda Ferreira (e-cadernos ces)
This paper explores the evolving concepts of ‘woman’ and ‘lesbian’ in contemporary discourse, emphasizing fluidity influenced by spatial, temporal, and power dynamics. Critiquing rigid identity politics, it advocates for a broader, inclusive perspective on lesbianism, challenging Western-centric views. Affirming lesbian identities, incorporating the fluidity of gender and sexual identities, is recognized as revolutionary, disrupting gender norms, and dismantling patriarchal structures. Lesbian erasure, rooted in societal expectations and patriarchy, is also experienced in LGBTIQ spaces with biases in the representation of different sexual orientations and gender identities. This paper calls for intersectional approaches, recognizing diverse voices, and active efforts to challenge and dismantle lesbian erasure for a more inclusive society.